Plumage and Fat Condition Scores as Well-Being Assessment Indicators in a Small Passerine Bird, the Zebra Finch (Taeniopygia guttata) - Kalnins, Lisa; Krüger, Oliver; Krause, E. Tobias (Frontiers in Veterinary Science, 2022)
The well-being of animals kept by humans in laboratories, farms, or as pets should always be of highest importance, and a prerequisite for this is adequate housing. To assess potential indicators for animal well-being, ideally simple, non-invasive and reliable methods are necessary. Here, we propose a novel plumage scoring system for small songbirds, using the example of the Zebra Finch, and examine its reliability in comparison with a well-known body condition index, i.e. the fat score. We used up to five different observers of different experience levels to assess inter- and intra-observer reliability of the proposed plumage score as well as the fat score. We found substantial inter-observer reliability for the proposed novel plumage score, and lower inter-observer reliability for the fat score, which seems to require more training of observers. The intra-observer reliability of the experienced observer who trained the others also showed a very strong reliability for the plumage score and for the fat score. Thus, we conclude that our proposed novel plumage score is a simple, reliable and non-invasive way to estimate an important indicator of captive Zebra Finches’ well-being. Furthermore, the plumage score can be reliably taught to other observers. The plumage score, maybe in combination with the fat score, may be an important tool to reliably assess well-being on a regular basis in captive populations in zoos, laboratories or pet stocks.